Autonomic and endocrine accompaniments of quantitative-qualitative blood pressure clusters in patients of Truskavets’ spa - Kozyavkina, Nataliya; Voronych-Semchenko, Nataliya; Vovchyna, Yuliya; Zukow, Walery; Popovych, Igor (Journal of Education, Health and Sport, 2020)
Background. Earlier we showed that profile patients of Truskavets’ spa are characterized by a wide range of blood pressure (BP) - from low norm to arterial hypertension III that correspond to the hemodynamics parameters. The purpose of this study is to clarify the autonomic and endocrine accompaniments of quantitative-qualitative BP clusters in the same contingent. Materials and methods. Under an observations were 44 patients with chronic pyelonephritis and cholecystitis in the phase of remission. Testing was performed twice - on admission and after 7-10 days of standard balneotherapy. The main object of the study was BP (tonometer “Omron M4-I”, Netherlands). The parameters of HRV ("CardioLab+HRV", Ukraine), plasma levels of Cortisol, Aldosterone, Testosterone, Triiodothyronine and Calcitonin (ELISA) as well as Ca-P marker of parathyroid hormone were determined. Results. In order to identify among the registered parameters, those for which the BP clusters differ from each other, a discriminant analysis was performed. The program forward stepwise included in the discriminant model 29 parameters. The most informative among them are HRV-markers of sympathetic tone and sympathetic-vagal balance as well as testosterone and cortisol, whose levels are maximal in patients with hypertension II, while minimal in patients with low norm BP, on the one hand, and markers of vagal tone and Kerdoe vegetative index, the levels of which are polar, on the other hand. The accuracy of patient classification is 98,9%. Conclusion. Autonomic and endocrine accompaniments of quantitative-qualitative blood pressure clusters corresponding to the existing ideas about the regulation of blood pressure.